Circular RNAs in vascular diseases - Liu, Qiaoyuan; Wang, Yaofeng; Zhang, Tinghong; Fang, Jianwen; Meng, Shu (Frontiers in Cardiovascular Medicine, 2023)
Vascular diseases are the leading cause of morbidity and mortality worldwide and are urgently in need of diagnostic biomarkers and therapeutic strategies. Circular RNAs (circRNAs) represent a unique class of RNAs characterized by a circular loop configuration and have recently been identified to possess a wide variety of biological functions. CircRNAs exhibit exceptional stability, tissue specificity, and are detectable in body fluids, thus holding promise as potential biomarkers. Their encoding function and stable gene expression also position circRNAs as an excellent alternative to gene therapy. Here, we briefly review the biogenesis, degradation, and functions of circRNAs. We summarize circRNAs discovered in major vascular diseases such as atherosclerosis and aneurysms, with a particular focus on molecular mechanisms of circRNAs identified in vascular endothelial cells and smooth muscle cells, in the hope to reveal new directions for mechanism, prognosis and therapeutic targets of vascular diseases.